Empowerment of Students of al-Qur’an Education Park al-Munawarah Pandanan Hadiluwih in Efforts to Memorize Asmaul Husna Using the Singing Method - Hikmawati, Hanifah; Khasanah, Siti Nur (LP3M STAI At-Tahdzib Jombang, 2024)
At Taman Pendidikan al-Qur’an al-Munawarah, Pandanan Hadiluwih Village, one of the challenges faced is improving the students’ ability to memorize Asmaul Husna, the 99 names of Allah which have special meaning and priority in Islam. To overcome this challenge, the singing method is used as an innovative approach to the memorization process. The singing method is a real learning approach that is able to make the female students of Taman Pendidikan al-Qur’an al-Munawarah Pandanan happy and happy, so that they are enthusiastic about reciting the al-Qur’an at Taman Pendidikan al-Qur’an. Children are guided in a psychological state to build a happy soul through tonal and rhythmic expressions which make the learning atmosphere more enjoyable. Learning will be easier to instill through songs because the lyrics are often repeated, so that when singing, children without realizing it train their memory. This method not only improves memorization skills but also motivates students and enriches their learning experience. Memorizing Asmaul Husna can also stimulate students’ love for Allah Swt, so that they can become a generation of believers, pious, Islamic and Qur’anic.